Elites rioplatenses del siglo XIX : Biografías, representaciones, disidencias y fracasos - Troisi Melean, J. (Comp.) (Estudios / Investigaciones, 2018)
Rioplatenses elites of the 19th century : Biographies, representations, dissidences and failures